PENERAPAN PEMBELAJARAN TSTS DENGAN AKTIFITAS WINDOW SHOPPING UNTUK MENINGKATKAN HASIL BELAJAR BANGUN RUANG SISI DATAR - Suprapto Suprapto (Universitas Muhammadiyah Pringsewu, 2017)
Abstract The implementation of TSTS learning with window shopping activities can foster student interest and improve mathematics learning outcomes. Students have extensive opportunities to work together and learn to communicate the results of their group discussions. The study aims to improve the learning outcomes of building flat side space. Subjects in this study were students of class VIII.4 SMP Negeri 3 Pringsewu Lesson Year 2014/2015. The study was conducted in 2 cycles, each cycle consisting of 3 meetings. The instrument used is the script about test and observation sheet of learning activities. To know the students' initial ability before being given the action the students are given pretest with the average result reaching 54,76. After the treatment, the average value of the test in the first cycle reached 69.86 and on the second cycle the average test value reached 80.88. In conclusion, the implementation of TSTS learning with window shopping activities can improve the learning outcomes of building the flat-side room of students of grade VIII.4 SMP Negeri 3 Pringsewu Lesson Year 2014/2015. Keywords:  Two Stay Two Stray, Window Shopping